Daily Variations in pCO2 and fCO2 in a Subtropical Urbanizing Lake - Yang, Rongjie; Chen, Yingying; Du, Jie; Pei, Xiangjun; Li, Jinghua; Zou, Zan; Song, Huixing (Frontiers in Earth Science, 2022)
The transfer of CO2 from lakes to the atmosphere is a component of the global carbon equilibrium, while the quantification of the CO2 partial pressure (pCO2) is critical for exploring the contribution of freshwater CO2 emissions in the regional/global carbon budget. To investigate the daily variability of pCO2 and CO2 fluxes (fCO2), we conducted in situ biweekly pCO2 detection at 7:00, 10:00, 14:00 and 17:00 China Standard Time (CST) from Jan. to Sept.2020 in the subtropical urbanizing Qinglonghu Lake in Chengdu, Sichuan, China. The pCO2 during the daytime varied greatly from 8.3 to 1061.3 μatm, with an average of 137.7 μatm, while the average pCO2 (n=11) clearly gradually decreased from 7:00 CST (204.9 ± 295.7 μatm) to 17:00 CST (93.5 ± 105.5 μatm). Similarly, the average fCO2 values were −19.3 (± 27.5), −24.8 (± 20.7), −29.2 (± 9.1) and −30.4 (± 10.7) mmol m2 h−1 at 7:00~17:00 CST, respectively. Further, we observed a negative correlation between pCO2 and water temperature and dissolved oxygen, but a positive correlation between pCO2 and total organic carbon and chlorophyll a. By a systematic overview of previously published data, we also discussed the differences and uncertainties in pCO2 and fCO2 estimates at regional and global scales. We therefore speculate that uncertainties may exist in the contributions of CO2 balance on lake surface in regional/global carbon budgets due to this daily pCO2 variation..